Symbolic Meaning of Debus Performance in the Belief of the Community of Sintuk, Lubuk Alung, Pariaman - Darmawati, Darmawati (Humanus, 2022)
This study aims to explain the symbolic meaning of the Debus performance in the belief of Sintuk community which is still firmly held today. This study belongs to qualitative research. The data were obtained from key informants, interviews, and documents. The collection of the data was conducted through participant observation and documentation. The data analysis technique consisted of data reduction, data display, and conclusions/verification making. The results of this study show that in the Debus performance, there is a performance structure which must be carried out. It contains elements of the performance, the completeness of the performance, and the behaviors of showing immunity which means rejecting misfortunes as believed by the Sintuk community.